EFECTOS JURÍDICOS Y ECONÓMICOS QUE CAUSA LA FALTA DE INFORMACIÓN AL MOMENTO DE ADQUIRIR UNA PÓLIZA EN UNA ASEGURADORA VEHICULAR - GRANDA GRANDA, MARÍA FERNANDA (2016)
Despite the comprehensive law framework that our country has been issued about contracts, it is clear that in relation to vehicle insurance, has a long way to educate the Ecuadorian assemblyman, given that those who have engaged in the business of provision of services by type of insurance, so even willful, incorporated in the contract clauses, some texts that end up hurting the insured, this problem is not an isolated issue, we find in everyday life and across the country. With unwavering purpose to substantiate the need to reform the General Law of Private Insurance of Ecuador, with respect to guaranteeing the rights of the contracting person's insurance policy for vehicles, the present research work, based on analysis performed theoretical, doctrinal and legal, primarily contracts insurance policies; in this direction using various research methods; and the use of techniques such as interviews and survey have developed this research, starting by defining some basic concepts such as: contract, insurance, insurance policies, contracts developments in the Company's behavior insurance contracts in Ecuadorian society. In order to achieve the fulfillment of my objectives, I relied on fieldwork through surveys and interviews aimed at legal practitioners from the city of Loja, as well as users of the contracts of insurance policies for vehicles. As for the conclusions and recommendations, these are derived from the answers given by respondents and interviewees; where it is found that most agree with the reform of the General Law of Private Insurance of Ecuador, in relation to contemplate contracts of insurance policies for vehicles, sufficient and clear information on coverage and limitations that offer insurance companies. Case studies, related to contracts of insurance policies for vehicles, it was determined that these insurers are introducing unreadable texts that harm the user or contractor of the insurance, when suffering a loss, thus justifying the need for revision this legislation. The small number of existing insurance companies in our country, as a result of the requirements for their creation, such as the requirement of a large capital limits other entrepreneurs choose to join the competition in this business, which in essence leads to the concentration of wealth in a few families are those that control the insurance market, imposing in most cases, conditions that usually end up hurting the contracting of insurance; on these considerations I raise my law reform.